The classification of chalcolithic and early Bronze Age copper and bronze axe-heads from southern Britain - Needham, Stuart ca. 20. Jh (Access archaeology, 2017)
This work presents a comprehensive classification of the morphology of early metal age axe-heads, chisels and stakes from southern Britain. It is illustrated by a type series of 120 representative examples